The impact of neoadjuvant relugolix on multi-dimensional patient-reported fatigue - Hsueh, Jessica Y.; Gallagher, Lindsey; Koh, Min Ji; Shah, Sarthak; Danner, Malika; Zwart, Alan; Ayoob, Marilyn; Kumar, Deepak; Leger, Paul; Dawson, Nancy A.; Suy, Simeng; Collins, Sean P. (Frontiers in Oncology, 2024)
Introduction Androgen deprivation therapy has been shown to improve cancer control when combined with radiotherapy. Relugolix is an oral GnRH receptor antagonist that achieves rapid profound testosterone suppression, which may increase the perception and/or impact of fatigue. This study sought to evaluate neoadjuvant relugolix-induced fatigue in prostate cancer patients prior to the start of stereotactic body radiation therapy (SBRT). Methods Relugolix was initiated at least two months before SBRT. The 13-item Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) questionnaire was collected at baseline and one hour prior to SBRT initiation. A five-point scale was used to score individual items. Overall scores range from 0-52 and individual item scores were converted to 0-100, with higher scores reflecting less fatigue. Five “experience” items explored self-perceptions of fatigue, and eight “impact” items sought to evaluate the effect of fatigue on daily activities. Items were evaluated for statistical significance (paired t-test, p < 0.05) and clinical significance (minimally important difference (MID); 0.5 standard deviation from baseline). Results Between March 2021 to December 2023, 89 men were treated at Georgetown with neoadjuvant relugolix and SBRT. Mean age was 71 years (range: 49-87). Median initiation of relugolix was 4.5 months prior to SBRT (range: 2-14.2 months). 93% patients achieved castration (testosterone levels ≤ 50 ng/dL) and 85% patients achieved profound castration (testosterone levels ≤ 20 ng/dL). 87 patients completed the FACIT-F questionnaire, with an average overall score of 45.6 at baseline and 41.0 at SBRT initiation. This difference was statistically and clinically significant (p < 0.01, MID = 3.55). Patients experienced an increase in fatigue for 12 of 13 items, with statistically significant changes for 11 items. Three of five experience items showed a clinically significant increase in fatigue. Only two of eight impact items were clinically significant. Discussion Our study shows that relugolix significantly increases fatigue, affecting multiple areas of life. While the fatigue does not appear to generally impact a patient’s ability to carry out normal activities, patients demonstrate frustration with being too tired for these activities. It is essential for clinicians to counsel prostate cancer patients on the impact of neoadjuvant relugolix on quality-of-life issues like fatigue.